The Identification of Primary School Students with Symptoms of Dyslexia, Their Academic Achievements and Discipline Problems - Devaraj, Sheila Christine (2003)
The purpose of this study was to come up with a diagnostic tool that can be used to identify students with symptoms of dyslexia and then to determine whether there was any significant correlation between symptoms of dyslexia in students and discipline problems. The target population was Standard 3 and Standard 4 students from national primary schools in the District of Klang. A total of 197 respondents were selected through cluster random sampling. Data was collected by carrying out a 10-Item Diagnostic Test. The test covered Rapid Naming, Bead Threading, Hearing Skills, Postural Stability, Phonemic Segmentation, 2- Minute Spelling, Backward Digit Span, One-Minute Writing, Verbal Fluency and Semantic Fluency. It took about thirty minutes to be administered to each student. The tests were then normed separately for the (104) Standard 3 and (93) Standard 4 students. Teacher nomination was used to identify students with discipline problems. The student’s academic achievement was based on their results in the mid-year examination using the average score in Mathematics, English and Bahasa Malaysia. The data was analysed by means of the Independent t-test and the Pearson’s product moment correlation. The Independent t-test was used to compare students who achieved zero (0) for their total score for symptoms of dyslexia with students who had a score ranging from 10 to 20. The test showed that there was significant difference in the academic achievement (t (50) =7.06, p<.05) of students with symptoms of dyslexia (M=33.83, SD=19.44) and students without symptoms of dyslexia (M=69.69, SD=19.43). There was a significant difference as well in the occurrence of discipline problems (t (50) =-8.13, p<0.05) among students with symptoms of dyslexia (M=3.24,SD=1.09) and students without symptoms of dyslexia (M=0.93, SD=1.11). In the correlation analysis, it was found that there was a significant negative correlation (substantial relationship) between academic achievement and symptoms of dyslexia for both the Standard 3 ( r (103) = -.603, p< .01) and the Standard 4 (r (89) = -.616, p< .01) students. The Pearson’s product moment correlation also showed that the relationship between discipline problems and symptoms of dyslexia was higher for the older students. The Standard 3 students had r = .387, p< .01 which is a definite but small relationship, while the Standard 4 students had r = .489, p< .01 which is a substantial relationship. This might indicate a trend where the contribution of symptoms of dyslexia to discipline problems increases as the student progresses through the school system. In the analysis of variance, it was found that there was no significant difference in the occurrence of discipline problems and students with symptoms of dyslexia among the Malays, Chinese and Indians. However there was a difference in terms of the socioeconomic status. The students who come from the higher SES families have the lowest dyslexic score (2.13) whilst having the highest academic achievement (70.40). The opposite is seen for students from the lower SES families who have the highest dyslexic score (6.36) whilst having the lowest academic achievement (44.41). The results also show a significant difference in discipline problems based on the SES. This is consistent with studies carried out by the Ministry of Education that show that indiscipline predominates in the urban poor and working-class groups (Rahimah & Norani, 1998). A comparison was also made between the boys and girls and the findings showed that there was no significant difference in the total dyslexic score between the two sexes. This is consistent with studies where measurement was based on the research identification and not on the basis of school identification. On the other hand, there is a significant difference in the occurrence of discipline problems when the boys (M=2.68, SD=1.51) were compared to the girls (M=1.64, SD=1.37). This study has contributed in some measure in establishing a diagnostic tool that can be used in schools to identify students with symptoms of dyslexia. Furthermore, by showing the correlation between symptoms of dyslexia to both academic achievement and discipline problems, it emphasises the importance of detecting students with symptoms of dyslexia as soon as possible so that appropriate remedial work and teaching methods can be applied.